Ethnicity and incidence of congenital hypothyroidism in the capital of Macedonia - Violeta Anastasovska; Mirjana Kocova (Walter de Gruyter GmbH, 2017)
Congenital hypothyroidism (CH) is a common and preventable cause of intellectual disability for which early diagnosis is difficult without newborn screening. Genetic and environmental factors, race, ethnicity, sex, and pregnancy outcomes were noted as risk factors. In the study we aimed to determine the incidence of CH among different ethnic groups in the capital of Macedoina - a multiethnic city.